Accuracy of Sterile and Non-Sterile CAD/CAM Insertion Guides for Orthodontic Mini-Implants - Ludwig, Björn; Krause, Luisa; Venugopal, Adith (Frontiers in Dental Medicine, 2022)
Aim: The aim of this study was to measure the transfer accuracy of computer-aided design/computer-aided manufacturing (CAD/CAM) insertion guides using mini-implants. The target value is the virtual planned position (100%). It is also clinically mandatory to use sterilised surgical guides (autoclaved at 137 °C). The results obtained using sterilised and non-sterilised insertion guides were compared. In addition, the actual position of the mini-implants, as implemented, was compared with the digitally planned positions. Materials and methods: Following CAD/CAM planning and production of 60 insertion guides made from synthetic resins that had been previously tested for suitability, 120 mini-implants were inserted, in pairs, in blocks of bone substitute material. Half of the insertion guides were sterilised while the other half non-sterilised. Compared with the position of the mini-implants in the digital plans, deviations in the apical and coronal distances between the mini-implants and insertion depth, as well as the included angle of the mini-implants to one another and to the surface of the bone substitute material were determined. Results: Post-sterilization, dimensional and material changes were observed. When compared, the deviations to the virtual planned position achieved when performing insertion using sterilised insertion guides were lower than those achieved when using non-sterilised insertion guides. Heat treatment during the sterilisation process improved the accuracy of the insertion guides. When comparing sterile insertion guides to the digital planned position (100%) the mean coronal deviation was 0.057 mm (0.81%), the apical deviation was 0.428 mm (6.11%) and insertion depth mean deviation at the right side was 0.15 mm (2.15%) while that on the left was 0.073 mm (1.04%). Conclusion: The CAD/CAM TAD insertion guide could not achieve 100% accuracy in translating the digital planned position into the real anatomic location. Deviations to the ideal position between 0.81% and 6.11% were observed. Clinically, for appliances that fit post mini-implant insertion, the coronal distance of the mid mini-implant head is the most important. At this point, the mean deviation to the planned positions is 0.81%, which is clinically acceptable and most likely reproducible by using CAD/CAM insertion guides.